2008
DOI: 10.1155/2008/157356
|View full text |Cite
|
Sign up to set email alerts
|

Studying Social Cognition in Patients with Schizophrenia and Patients with Frontotemporal Dementia: Theory of Mind and the Perception of Sarcasm

Abstract: We investigated social cognition and theory of mind in patients with schizophrenia and in patients with frontotemporal dementia in order to elucidate the cognitive mechanisms involved in the breakdown of these skills in psychiatric and neurological patients. Our tasks included videotaped scenarios of social interactions depicting sincere, sarcastic and paradoxical remarks, as well as lies. We found impaired performance of the schizophrenia group on all theory of mind conditions despite their intact understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 19 publications
2
37
0
2
Order By: Relevance
“…Dozens of case studies and between group comparisons have provided empirical support for the clinically described social cognitive deficits in bvFTD including impaired ability to process facial emotions (Cavallo et al, 2011; Gleichgerrcht et al, 2002; Miller et al, 2012; Torralva et al, 2009), detect socially inappropriate speech (Gleichgerrcht et al, 2010; C. Gregory et al, 2002; Torralva et al, 2009), adopt the perspective of another person (Adenzato et al, 2010; Eslinger et al, 2011; C. Gregory et al, 2002; Lough et al, 2001; Lough & Hodges, 2002), solve social dilemmas (Eslinger et al, 2007), perceive sarcasm (Kosmidis et al, 2008), or react to fearful or sad stimuli (Sturm et al, 2006; Werner et al, 2007). …”
Section: Social Cognition In the Diagnosis Of Ftd Syndromesmentioning
confidence: 99%
“…Dozens of case studies and between group comparisons have provided empirical support for the clinically described social cognitive deficits in bvFTD including impaired ability to process facial emotions (Cavallo et al, 2011; Gleichgerrcht et al, 2002; Miller et al, 2012; Torralva et al, 2009), detect socially inappropriate speech (Gleichgerrcht et al, 2010; C. Gregory et al, 2002; Torralva et al, 2009), adopt the perspective of another person (Adenzato et al, 2010; Eslinger et al, 2011; C. Gregory et al, 2002; Lough et al, 2001; Lough & Hodges, 2002), solve social dilemmas (Eslinger et al, 2007), perceive sarcasm (Kosmidis et al, 2008), or react to fearful or sad stimuli (Sturm et al, 2006; Werner et al, 2007). …”
Section: Social Cognition In the Diagnosis Of Ftd Syndromesmentioning
confidence: 99%
“…Studies have also shown that bv-FTD patients have difficulties in identifying social concepts, judging the appropriate plan of action in social dilemmas, recognising sarcasm and differentiating minor social transgressions from serious moral violations 52 53 57 59–62. Imaging studies have suggested that poor moral judgement and socio-pathic behaviour in bv-FTD may be linked to involvement of the MFC and right temporal lobe, regions believed to play a critical role in social cognition 2 61 63 64…”
Section: Social Cognition In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Zahn et al (2009) examined context-dependent knowledge of social concepts in patients with frontal-temporal lobar degeneration, finding that they are particularly impaired on such tasks. Nonliteral language interpretation has also been studied with respect to interpretation of sarcasm (as opposed to proverb interpretation) in bvFTD patients (Kipps, Nestor, Acosta-Cabronero, Arnold, & Hodges, 2009;Kosmidis et al, 2008;Rankin et al, 2009), wherein bvFTD patients were observed to have significantly more trouble comprehending sarcasm, compared to healthy controls and AD patients, and, this was attributed to frontal lobe dysfunction.…”
Section: Introductionmentioning
confidence: 99%